Consumer Behavior in Purchasing Products Online at the Tokopedia Marketplace - Suwasono, Edy (Prosiding Seminar, 2020)
The purpose of this study (1) Knowing how marketing stimuli encourage consumers to make purchases online at Tokopedia, (2) individual characteristics encourage consumers to make purchases online at Tokopedia. (3) the process of consumers deciding to make an online purchase at Tokopedia. Determination of the subject by purposive sampling. data collection: interviews, observation techniques and observation techniques. The method used is descriptive method through a qualitative approach, data analysis, namely data reduction, data display and conclusion drawing / verification. Research results Some of the main factors of marketing stimulation that encourage consumers to shop online at Tokopedia are the ease of getting an item The main factor in product selection is based on positive reviews / reviews / testimonials from other buyers about the product. Brand selection is driven by brand loyalty and if there are better products with positive reviews, consumers will try to buy with a new brand that has positive reviews